Rehabilitation single tooth loss with screw retained implant crown: Case report - Jane Amelia (Maranatha Christian University, 2021)
Tooth loss is a common problem in adults. the negative effects of tooth loss are decreased chewing and speech function, reduced aesthetics, and migration of adjacent teeth. Many types of dental prosthetics can be used to prevent these negative effects, such as removable partial dentures, adhesive resin dentures, fixed partial dentures, and dental implants each prosthesis had its advantages and disadvantages. In this case report the clinician will discuss about single tooth implants. The aim of this case report is to provide information about the procedure for placement single tooth implants to the posterior mandibular teeth using the screw retained implant technique.